Sex Education For Millenial in Islamic Perspective - Alfurqan Alfurqan; Sari Narulita; Fitri Oviyanti; Fauza Masyhudi (PALAPA, 2022)
Sex education is an effort to teach, raise awareness, and provide information about sexual problems. Sex education is very important to give to adolescents or what is often called the millennial generation. This study aims to determine: Attitudes or behaviour of the millennial generation towards various sexual problems around them and how Islam and its legal sources talk about the importance of sex education and whether there are differences in the level of understanding of sex education from an Islamic perspective. Research using a qualitative approach is the study of literature, by digging various information regarding sex education in millennials, the results are obtained, first: sex education should be considered as part of the educational process to strengthen the development of millennial personality. Second, parents have an important role to overcome deviant sexual behaviour is the way parents teach sex education directly and continuously to children as early as possible in the family according to Islamic teachings and local community norms so that the millennial generation accepts their sexuality which is an integral part of their lives with full of responsibility.